(untitled) (Research, Society and Development, 2020)
The search for high levels of productivity has resulted each year in the launch of new products for use in all stages of the production process. In this context, the treatment of seeds with insecticides and fungicides is already a consolidated practice, but the use of micronutrients and the launch of new products raise doubts for producers. Thus, the objective of the work was to evaluate the effect of seed treatment with different fungicides, insecticides and micronutrients on the phytotechnical parameters of soybean development and productivity. Nine seed treatments available on the local market were used, and after sowing the parameters of crop development were evaluated, as well as the productive parameters after the crop reached physiological maturation. The results indicate that the different seed treatments used affect the physiological characteristics of seeds and seedlings after emergence, with all values being higher than untreated seeds (Control) and also the weight of a thousand grains and morphological characteristics, however, in climatic conditions evaluated, there was no difference in the final crop yield.